Barium- and strontium-enriched (Ba0.5Sr0.5)1+xCo0.8Fe0.2O3-d oxides as high-performance cathodes for intermediate-temperature solid-oxide fuel cells - Zhou, W.; Ran, R.; Shao, Zongping; Zhuang, W.; Jia, J.; Gu, H.; Jin, W.; Xu, N. (Pergamon Press, 2008)
(Ba0.5Sr0.5)1+xCo0.8Fe0.2O3-d, or BSCF(1 + x), (0 = x = 0.3) oxides were synthesized and investigated as cathodes for intermediate-temperature solid-oxide fuel cells. The A-site cation excess in BSCF(1 + x) resulted in a lattice expansion and the creation of more active sites for oxygen reduction reaction due to the lowered valence states of the B-site ions and the increased oxygen vacancy concentration, which improved the oxygen adsorption process. On the other hand, the A-site excess could also result in higher resistances for oxygen adsorption (due to the formation of BaO and/or SrO impurities), and oxygen-ion transfer (by facilitating the solid-phase reaction between the cathode and the electrolyte). By taking all these factors into account, we found BSCF1.03 to be the optimal composition, which lead to a peak power density of 1026.2 ± 12.7 mW cm-2 at 650 °C for a single cell. © 2008 Acta Materialia Inc.